NILAI-NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERPEN PADA SUATU SENJA AKU JATUH CINTA KARYA MAYA LESTARI G.F. - Chairunnisa, Natasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
AbstractThis research aims to improve the reader"™s understanding of the value of character education in the short story Pada Suatu Senja, Aku Jatuh Cinta by Maya Lestari G.F. This research is qualitative with descriptive method. The data source of this research is the short story Pada Suatu Senja, Aku Jatuh Cinta by Maya Lestari G.F. with data in the form of quotations of words, phrases and sentences that lead to the object of analysis. The results showed that the data obtained amounted to 25 data. The values of religious obtained are worship, recitation of the Qur"™an, funeral and pray. The values of nationalism obtained are love homeland, work hard for the welfare of the people, and anti-comunism. The values of self-reliance obtained are strong, work ethic, and self-determination. The values of mutual cooperation obtained is cooperation. The values of integrity obtained are consistent and responsible for decisions. The implementation plan of learning the results of this research combined with Indonesian language learning in grade XI high school/equivalent level in the curriculum 2013 with KD 3.2. comparing short story texts both oral and   written and KD 4.2. producing short story text that are coherent in accordance with the characteristics of the text both verbally and in writing.Keywords: value, character education, short stor